2008
DOI: 10.1086/529141
|View full text |Cite
|
Sign up to set email alerts
|

Mumps Vaccine Performance among University Students during a Mumps Outbreak

Abstract: High 2-dose MMR coverage protected many students from developing mumps but was not sufficient to prevent the mumps outbreak. Vaccine-induced protection may wane. Similar US settings where large numbers of young adults from wild-type naive cohorts live closely together may be at particular risk for mumps outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 14 publications
2
83
1
1
Order By: Relevance
“…Although the goal of vaccination is to establish durable, lifelong immunity, it has become clear that for a number of infectious diseases, vaccine-induced host protective immunity wanes over time (4)(5)(6)(7)(8)(9)(10). Participants in an NIAID-sponsored workshop, "Waning Immunity and Microbial Vaccines," reviewed research on six representative vaccines and assessed the issue of waning immunity and possible approaches to generate long-term protection.…”
mentioning
confidence: 99%
“…Although the goal of vaccination is to establish durable, lifelong immunity, it has become clear that for a number of infectious diseases, vaccine-induced host protective immunity wanes over time (4)(5)(6)(7)(8)(9)(10). Participants in an NIAID-sponsored workshop, "Waning Immunity and Microbial Vaccines," reviewed research on six representative vaccines and assessed the issue of waning immunity and possible approaches to generate long-term protection.…”
mentioning
confidence: 99%
“…5,23 In Finland, where indigenous mumps has been declared to be eliminated, Davidkin et al were able to follow individuals who received the MMR vaccine. 24 The authors found that 20 y after the first dose, 74% were seropositive for mumps (lower than 95% for measles and 100% for rubella).…”
Section: Discussionmentioning
confidence: 99%
“…Although the VE of longer time-periods since vaccination are mostly not statistically significant, this study also suggests that mumps VE may decline nine years after vaccination, and previous studies also documented increased risk of developing mumps with increasing time after vaccination. 9,21 The second dose of mumps-containing vaccination campaign should be added in the national schedule, may be performed in ~11 y old. Otherwise, providing catch-up vaccination opportunities for older children who were not eligible for the national vaccination schedule also would increase vaccination coverage in the age groups most affected by mumps.…”
Section: Mmr or MM Vaccine Has Been Included In The Nationalmentioning
confidence: 99%